Camel Milk and the Prevention of Glucose Cataract, an Organ Culture Study - Alghamdi, Ali H.S.; Mohamed, Hasabelrasoul; Mohamed, Hasabelrasoul; Austin, Jonathan; Henry, Collin; Massey, Kayla; Sayied, Shanzeh; Sledge, Samiyyah; Williams, Aliza (Journal of Nutritional Therapeutics, 2018)
Purpose: To test if camel milk affects glucose-induced opacity in organ cultured rat and human lenses. Methods: Whole human and rat lenses were cultured in various media containing either 55 mM glucose, camel milk, or a combination of both glucose and milk. Some lenses were cultured in a media containing neither moiety to establish a control. Absorbance spectra of human and rat lenses were measured daily using a visible/ultraviolet light spectrometer. Lens opacities were graded by a blinded grader from photographs taken daily. Aldose reductase activity, catalase activity, glutathione and receptor for advanced glycation end products levels were assayed. Results: The optical density and light scattering intensity of human lenses cultured with glucose were higher after two to four days in organ culture compared with lenses cultured without glucose. Camel milk in the culture media attenuated the glucose-induced increase in optical density, light scattering intensity and opacity grade after two to four days for both human and rat lenses. Aldose reductase activity, catalase activity and glutathione levels were restored but the receptor for advanced glycation end products was similar in rat lenses cultured with glucose compared with those cultured with glucose and camel milk. There were no differences between the assayed moieties in human lenses cultured with glucose or glucose plus milk. Since camel milk restored rat lens glutathione levels, it is possible that camel milk may protect the lens from oxidation and significantly reduce the glucose-induced increase in light scattering of human lenses. Structurally and physiologically, rat lenses are distinct from human lenses, therefore, the rat lens data was highly variable when compared with the human lens data, highlighting the importance of using human lenses in future studies. Conclusions: Camel milk present in the organ culture medium inhibited the glucose-induced opacity in human lenses and restored the amount of glutathione to the same levels of lenses not cultured in glucose. The positive results of the current study leads to future studies to determine the moieties in camel milk that are responsible for cataract inhibition and in vivo studies involving camel milk.